Effect of whey protein concentrate on the quality of smoked chicken sausages from broiler spent hens - Rao, K H; Anjaneyulu, A S R; Singh, R R B; Dubey, P C; Yadav, P L (The Indian Journal of Animal Sciences, 2012)
Quality of smoked chicken sausages formulated with broiler spent hen meat and edible byproducts in natural proportion and different levels of whey protein concentrate (WPC) was examined. The edible components available for product processing were 67% lean meat, 11.4% fat, 19% skin and 2.6% gizzard and heart. Addition of WPC at 1.5% significantly (P